Left ventricular platelet deposition after acute myocardial infarction. An attempt at quantification using blood pool subtracted indium-111 platelet scintigraphy. Issue 5 (November 1984) - Verheugt, F W; Lindenfeld, J; Kirch, D L; Steele, P P
Abstract : Since indium-111 platelet scintigraphy for the detection of left ventricular thrombosis often shows considerable non-specific blood pool activity a subtraction method using simultaneous technetium-99m blood pool scintigraphy was undertaken in 11 subjects with well documented remote myocardial infarction, who served as positive or negative controls, and in 18 consecutive patients with acute myocardial infarction. The results were compared with those of cross sectional echocardiography. Thirteen patients had transmural myocardial infarction and the calculated count per pixel in the left ventricle of the subtracted indium-111 platelet scintigram was (mean (SD)) 0.28(0.35), but five patients with subendocardial myocardial infarction had a mean count of 0.04(0.06). In seven patients with transmural myocardial infarction (two anterior and five inferior) left ventricular thrombosis was detected by indium-111 platelet scintigraphy but in only one of these by cross sectional echocardiography. None of the patients with subendocardial myocardial infarction had left ventricular thrombosis. Subtracted left ventricular counts correlated well with the visual results. It is concluded that left ventricular platelet sequestration after acute myocardial infarction may be quantified and precisely located and that quantitative longitudinal studies of the natural history and drug intervention are now possible.